Peran Moderasi Motivasi Kerja Pada Pengaruh Beban Kerja Terhadap Kinerja Karyawan - Ananda, Rekizal; Handayani, Susi (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2024)
This study aimed to determine and analyze the effect of workload on employee performance moderated by work motivation at PT Pelindo Multi Terminal (Persero) Belawan. This study uses an associative approach, namely research conducted, to determine the influence or relationship between the independent and dependent variables. The population and sample of this study are all employees at PT Pelindo Multi Terminal (Persero) Belawan, totaling 61 people. The data collection technique used in this study was a questionnaire. The data analysis technique used is the partial least square–structural inquiry model (PLS-SEM. Data processing in this study uses the PLS (Partial et al.) software program). The results of this study indicate that workload has a significant effect on employee performance and work motivation can moderate the effect of workload on employee performance at PT Pelindo Multi Terminal (Persero) Belawan